Evaluation of TCP Acknowledgment Mechanism Influence on Router Performance - Pavilanskas, L.; Statkus, A. (Elektronika ir Elektrotechnika, 2010)
The efficient usage of congestion control becomes significant as Internet traffic grows. The quality of congestion control greatly affects utilization efficiency of the data network equipment. This paper presents detailed analysis of interaction between congestion control and acknowledgment mechanism functions. Also analysis of possibilities to reduce the number of ACK messages with ACK filtering is presented. The presented results of experiments with real network are shows that data network router performance, without any considerable influence to TCP functionality can be significantly increased when the ACK filtering is used.